APLIKASI UJI COBA SKALA LABORATORIUM IMPLEMENTASI PROTOTYPE ALAT INOVASI TEKNOLOGI PASCA PANEN BERBASIS BIOMASSA UNTUK DETEKSI TEMPERATURE DENGAN SISTEM INTERNET OF THINGS - Melyna Handayani; Juandi Muhammad (Universitas Riau, 2022)
Digital technology in the form of a drying oven is used for the drying process of a sample biomass fuel. There are 2 types of biomass used, namely Coconut Shell and Acacia tree branches. The biomass is used as fuel for the drying process in the drying oven. This study aims to analyze a change in temperature, humidity and heat with various mass variations in coconut shells and acacia tree branches. Mass variations used are 1000 gr, 1500 gr, 2000 gr, 2500 gr, and 3500 gr. The research process begins by burning biomass from the first mass variation to the last mass variation. Furthermore, in the process of burning biomass, the resulting data is accessed via the internet of things seen from a website. The results of the data have a time span of 5 minutes for each observation of temperature and humidity. The data results are the comparison of time with internal temperature on coconut shells with the highest temperature of 93.7°C with a long burning time of 440 minutes, while on wood twigs the highest temperature is 93.7°C and the time required for the combustion process is 445 minutes. The best heat produced in coconut shell of 3500 gr with a maximum heat of 377.43 Joules at an internal temperature of 61.8°C for 45 minutes. Acacia tree branches have the best calorific value with a mass of 1000 gr, it’s maximum heat of 288.82 Joules at 37.7°C for 10 minutes.